Estudo da interação entre borrachas comerciais e misturas de biodiesel/diesel por espectroscopia de ressonância magnética nuclear - Silva, Lorena Mara Alexandre e (Universidade Federal de São Carlos, 2014)
Nowadays biodiesel has taken steps toward the consolidation as energetic matrices of many countries. Elastomers are one of the most important groups of materials used in engines and the compatibility of these materials with biodiesel is a growing concern. Thus, to correlate important information about compartmentalized phases of rubber/fuel system, low and high field NMR and emerging technologies such as hybrid NMR probe and imaging through mass spectrometry (DESI), were employed. This work permitted, for the first time, to understand the structural and chemical changes that diesel and mainly biodiesel induces in the structure of vulcanized rubber. For natural rubber (NR), the low-field NMR experiments have shown that the damage did not occur at the polymer crosslinking but biodiesel mostly affects the interaction between the filler and rubber. The high resolution NMR also allowed verifying the exudation of the filler and filler aggregates. The use of Comprehensive Multi-Phase NMR applied to NR, nitrilic rubber (NBR), styrene-butadiene rubber (SBR) and ethylene-propilene-diene rubber (EPDM), permitted to study the different phases coexisting in the complex fuel/rubber system as well as the interface between these phases. These data indicated that the carbon black aggregates are being exudate and thus, the demand for fillers with higher affinity with the elastomers seems to be one of the most important parameters in the search for materials more compatible with biodiesel. Thus, in molecular level it can be seen that the elastomer less affected by the presence of biodiesel was EPDM, followed by SBR, NR and NBR. Besides it was observed the inclusion of biodiesel molecules into the EPDM structure, in contrast to other data in literature. This finding can infer about the long-term degradation of the elastomeric structure. Furthermore, DESI demonstrated that biodiesel trapped at the EPDM is in the oxidized and unoxidized forms, and probably this oxidation has a greater effect on the structure of the rubber.
Study of interaction between commercial rubber and mixtures of biodiesel/diesel through nuclear magnetic resonance spectroscopy
Keywords: Química orgânica; Biodiesel; Borracha; Ressonância magnética nuclear; CIENCIAS EXATAS E DA TERRA::QUIMICA